Does Phosphodiesterase Inhibition Lessen Facial Flap Necrosis in Tobacco Cigarette Users? - Pfaff, Miles; Shah, Ajul; Steinbacher, Derek (Facial Plastic Surgery, 2014)
Tobacco cigarette smoking remains a serious risk factor for necrosis of local facial skin flaps. To date, no pharmacological therapies exist for cigarette smoke-induced impairment of skin flap tissue survival. Accumulating evidence suggest that phosphodiesterase-5 (PDE-5) inhibitor therapy may counteract the negative effects of cigarette smoke on flap survival. Here, we evaluate skin flap survival in a series of consecutive tobacco cigarette users treated with the PDE-5 inhibitor, sildenafil, who underwent local flap facial reconstruction. We included 11 patients (5 females; median age: 64) with a significant smoking history. Seventeen facial flaps were performed for 14 defects. All patients received sildenafil in the postoperative setting. One complication of necrosis of the flap distal margin was encountered. Follow-up was available for all patients. Our results demonstrate that facial reconstruction in tobacco cigarette smokers can be performed with improved success and that sildenafil therapy may mitigate the deleterious effects of smoking on flap survival.
Keywords: phosphodiesterase-5 inhibitor; PDE-5 inhibitor; facial flap; local flap; flap necrosis; flap failure; tobacco; smoking; sildenafil